Responses to mass shooting events: The interplay between the media and the public. Issue 1 (30th January 2020) - Croitoru, Arie; Kien, Sara; Mahabir, Ron; Radzikowski, Jacek; Crooks, Andrew; Schuchard, Ross; Begay, Tatyanna; Lee, Ashley; Bettios, Alex; Stefanidis, Anthony
Abstract : Research Summary: Public mass shootings tend to capture the public's attention and receive substantial coverage in both traditional media and online social networks (OSNs) and have become a salient topic in them. Motivated by this, the overarching objective of this paper is to advance our understanding of how the public responds to mass shooting events in such media outlets. Specifically, it aims to examine whether distinct information seeking patterns emerge over time and space, and whether associations between public mass shooting events emerge in online activities and discourse. Towards this objective, we study a sequence of five public mass shooting events that have occurred in the United States between October 2017 and May 2018 across three major dimensions: the public's online information seeking activities, the media coverage, and the discourse that emerges in a prominent OSN. To capture these dimensions, respectively, data was collected and analyzed from Google Trends, LexisNexis, Wikipedia Page views, and Twitter. The results of our analysis suggest that distinct temporal patterns emerge in the public's information seeking activities across different platforms, and that associations between an event and its preceding events emerge both in the media coverage and in OSNs. Policy Implication: Studying the evolution of discourse in OSNs provides a valuable lens to observe how society's views on public mass shooting events are formed and evolved over time and space. The ability to analyze such data allows tapping into the dynamics of reshaping and reframing public mass shooting events in the public sphere and enable it to be closely studied and modeled. A deeper understanding of this process, along with the emerging associations drawn between such events, can then provide policy and decision‐makers with opportunities to better design policies and communicate the significance of their goals and objectives to the public.